Vitreous Hemorrhage following High-Altitude Retinopathy - Arjun Shrestha; Rinkal Suwal; Biju Shrestha (Case Reports in Ophthalmological Medicine)
Purpose. To report a case of high-altitude retinopathy with vitreous hemorrhage. Methods. An apparently healthy 29-year-old boy presented with a history of floater and slight diminution of vision in the left eye after climbing the mountain 4760 meters high. Results. The visual acuity at presentation was 20/20 in the right eye and 20/30 in the left eye. Anterior segment findings of both eyes were unremarkable. Fundus evaluation revealed bilaterally dilated major retinal veins. The right eye revealed clear, quiet vitreous, healthy macula, and pink and smooth optic disc. There was fresh vitreous hemorrhage confined just one disc diameter away at the superior and inferior part of the optic nerve in the left eye. The macula and optic nerve head of this eye grossly looked normal. Complete blood count, haemoglobin, ESR, CRP, sugar, renal function test, lipid panel, and serology for HIV, HCV, VDRL, and HBsAg were normal. The Mantoux test and chest X-ray also revealed normal findings. Physician consultation did not reveal other abnormalities. On the 3rd week of follow-up, his vision was 20/20 in both eyes. Fundus examination revealed clear vitreous in both eyes though some venous dilation and tortuosities were still evident in the left eye. A macular OCT scan showed almost normal-appearing fundus. Conclusions. Vitreous hemorrhage following climbing high altitude can be one of the manifestations of high-altitude retinopathy.